Efeitos do treinamento combinado sobre a força, massa muscular, resistência e potência aeróbica de idosas - Guedes, Janesca Mansur (2011)
Aging brings itself several modifications, including the progressive decline of physiological functions of the body, which can be brightened up by physical exercises. Both strength training but a program of aerobic resistance are important to avoid functional decline associated with age. This study aims to evaluate the effects of combined training program (strength training and aerobic resistance) on the grip strength, muscle mass, strength and aerobic endurance of elderly people. Thirty-five women (65.7 ± 6.68 years) were divided into three groups: combined training (CT, n = 15), endurance training (ET, n = 10) and aerobic training (AT, n = 10). Each group has trained twice a week; the CT group trained once a week strength and aerobic once for eight weeks. Before and after the training period, the participants were evaluated for grip strength, muscle mass of wide lateral femoral and rectum muscles (by ultrasound exam), power and endurance aerobic (by ergospirometric evaluation. In CT group there was an increase in manual right and left hands in grip strength, p = p = 0.001 and 0.004 respectively; in an aerobic endurance a p = 0.022 and in aerobic endurance a p = 0.014 both significant; There was difference statistically significant in increasing muscle mass of the wide lateral femoral with a p = 0.010, whereas in the femoral rectum there have been no significant difference. ET and AT groups also had statistically significant difference in all of these variables. The results suggest that there wasn t the phenomenon of interference and the current results indicate a training program which combines once a week aerobic and resistance exercise and once a week for the endurance exercise is so effective in delivering improvements in grip strength, power peak, aerobic endurance and musculature on training held twice a week of aerobic or strength only